2018
DOI: 10.1001/jamaophthalmol.2018.0185
|View full text |Cite
|
Sign up to set email alerts
|

Presentation of TRPM1-Associated Congenital Stationary Night Blindness in Children

Abstract: night blindness (CSNB) implies a stable condition, with the major symptom being nyctalopia present at birth. Pediatric clinical presentation and the course of different genetic subtypes of CSNB have not, to our knowledge, been well described in the era of molecular genetic diagnosis. OBJECTIVE To describe the presentation and longitudinal clinical characteristics of pediatric patients with molecularly confirmed TRPM1-associated complete CSNB (cCSNB).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 60 publications
(147 reference statements)
1
17
0
Order By: Relevance
“…Strabismus has in several cases been successfully treated by vision therapy or surgery. Notably, the clinical findings of our patients are consistent with a recently described large cohort of TRPM1 -associated CSNB in children 15 .…”
Section: Discussionsupporting
confidence: 91%
“…Strabismus has in several cases been successfully treated by vision therapy or surgery. Notably, the clinical findings of our patients are consistent with a recently described large cohort of TRPM1 -associated CSNB in children 15 .…”
Section: Discussionsupporting
confidence: 91%
“…Visual symptoms primarily include night blindness with decreased visual acuity, refractive errors, nystagmus, or strabismus [ 3 ]. A recent study suggested that children with CSNB may present without complaints of night blindness [ 4 ]. In addition, these symptoms can overlap with other progressive IRDs, such as cone–rod dystrophies; thus, accurate diagnosis is essential to predict future visual outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that Riggs type patients present relatively mild visual symptoms, such as restricted night blindness but normal photopic visual acuity, slight myopia, and no nystagmus [ 3 ]. The complete form of the Schubert–Bornschein type involves some notable pathogenic genes, such as X-linked recessive NYX (leucine-rich proteoglycan nyctalopin) [ 18 , 19 , 20 ], autosomal recessive GRM6 [ 21 , 22 ], TRPM1 [ 4 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], GPR179 [ 31 , 32 ], and LRIT3 [ 33 ], affecting signal transduction in the selective rod ON bipolar cell postsynaptic signal loss pathway. Typically, these complete type patients show moderate visual symptoms, including decreased visual acuity and high myopia.…”
Section: Introductionmentioning
confidence: 99%
“…The manifestation of the disease may include loss of night vision and decreased visual field, eventually progressing to blindness. CSNB is a group of heterogeneous genetic disorders of the retina that manifest as non-progressive nyctalopia [ 124 ]. Finally, AMD is a complex disease that exhibits several different pathological mechanisms including degeneration of photoreceptors and RPE cells causing visual impairment [ 125 ].…”
Section: Polyphenols Effects In Retinal Degenerative Diseasesmentioning
confidence: 99%